2010
DOI: 10.1063/1.3360847
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophilicity to superhydrophobicity transition of CuO nanowire films

Abstract: The surface of CuO is known for its hydrophilicity and exhibits superhydrophilic nature as nanowires are present. When exposed in the air at room temperature or treated by low temperature annealing, however, transition from superhydrophilicity to superhydrophobicity of the CuO nanowire films are observed. Since the chemical structure of the films after treatment remains the same as CuO according to x-ray photoelectron spectroscopy spectra, the superhydrophobicity may be attributed to partial deoxidation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(111 citation statements)
references
References 11 publications
6
105
0
Order By: Relevance
“…Chang et al 7 have studied the wettability transition of CuO nanowire films and found that when the hydrophobic CuO substrate was annealed in air at 350 C, the hydrophilicity was recovered. Several papers also confirmed that low temperature annealing could remove the surface modified monolayer.…”
Section: Annealing Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chang et al 7 have studied the wettability transition of CuO nanowire films and found that when the hydrophobic CuO substrate was annealed in air at 350 C, the hydrophilicity was recovered. Several papers also confirmed that low temperature annealing could remove the surface modified monolayer.…”
Section: Annealing Experimentsmentioning
confidence: 99%
“…Kietzig et al 8 proposed the decomposition of carbon dioxide into carbon with active magnetite which was created in the laser nanostructuring process as a potential explanation. However, there seems no well accepted theory to explain this behavior because this conversion existed widely in all kinds of metal oxides, including the oxides of Cu, 7 Fe, 8 Ni, 5 Ti, 9 and Zn. 10 In this paper, we aim to clarify the mechanism underlying the wettability transition of picosecond laser microstructured copper surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, efforts have been made to fabricate multifunctional superhydrophobic surfaces based on semiconductor oxide materials such as ZnO [12,13], TiO 2 [14,15], and CuO [16,17]; many researchers have chosen TiO 2 to fabricate superhydrophobic surfaces due to their controllable structure, biocompatibility, and desirable stability. Aytug et al [18] fabricated superhydrophobic ceramic coatings by phaseseparated nanostructured composite TiO 2 -Cu 2 O thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts have been made to fabricate multifunctional superhydrophobic surfaces based on semi-conductor oxide materials such as ZnO [16], Fe 2 O 3 [17], TiO 2 [18] and CuO [19]. TiO 2 nanostructures have become a focus of tremendous interest due to their unique physicochemical properties and good chemical stability related to applications including photocatalysis [20], anti-ultraviolet protection [21] and chemical sensor [22].…”
Section: Introductionmentioning
confidence: 99%